Description of Lymphocyte Levels in Typhoid Fever Patients at H. Andi Sulthan Daeng Radja Regional Hospital, Bulukumba Regency - Masba, A. Anisa; Fatimah, Fatimah; AB, Aszrul; Asdinar, Asdinar (CV. Science Tech Group, 2024)
Typhoid fever is a systemic infectious disease characterized by fever and abdominal pain due to the spread of Salmonella bacteria. Lymphocytes are a type of agranulocyte leukocytes that have various functional roles related to immune reactions to attacks by microorganisms, foreign macromolecules, and cancer cells. The purpose of this research is the describe of lymphocyte levels in typhoid fever patients at H. Andi Sultan Daeng Radja Regional Hospital, Bulukumba Regency. This study is descriptive to see the picture of lymphocyte levels in typhoid fever patients. This study uses a total sampling technique where the samples taken were 50 patients. The results of the study showed that 22 patients (44%) had high lymphocytes (lymphocytosis), 11 patients (22%) had normal lymphocytes, and 17 patients (34%) had low lymphocytes (lymphopenia). Of the 50 patients, 22 patients (44%) had a high lymphocyte count (lymphocytosis), based on age and gender, the largest number were those aged <11 years, 27 people (54%), and 29 women (58%).